(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2015)
After Indonesia, Singapura,Thailand and Vietnam, Malaysia is also has enacted specific laws regarding competition. The Competition Act 2010 was passed by the Malaysian Parliament and came into force in 2012. The Malaysian Competition Comission, which was formed under the Competition Comission Act 2010, is a body tasked with the enforcement of the provisions contained in the Competition Act 2010. Through the Competition Act 2010, Malaysia aims to improve the economy through competitiveness, and aims to protect the consumer. On the whole, the Competition Act 2010 prevents businesses from being involved in two types of activities, i.e. anti-competitive agreement and abuse of a dominant position in the market. With the existence of the Competition Act 2010, the government hopes that anti-competitive activities can be avoided. Therefore, this research was carried out to analyse the provisions contained in the Competition Act 2010. The aim of this research is to identify the provisions in the Conmpetition Act 2010, as well as to analyse the implementation of these provision in the Malaysian business sector. A qualitative approach was employed, that is, an analysis of relevant documents. The findings of the study are that the Competition Act 2010 provides the basis for a healthy competitiveness in a variety of commercial activities and general applications. Keywords: Competition Act 2010, Competition Commission Act 2010, anti-competitive agreement, dominant position